Análise da satisfação com o cateterismo vesical intermitente limpo - Greghi, Eliana de Fatima Martins (2022)
Introduction – Health education, in this study, was directed to the capacitation of patients to use the hydrophilic pre-lubricated catheters and their motivation to join the CIVC. Objective – To compare the usage aspects of two bladder catheters for a person with post urination residue in the CIVC. Method. Fifty patients took part in this study. They have post urination residue and use clean intermittent vesical catheterization. Two lubricated catheters of different technologies were used for seven days, six vesical catheterization a day, and they were evaluated by filling an instrument of percepction of customer satisfaction. Results – The set for CIVC resulted in greater satisfaction on participants, considering the attributes evaluated. Concerning the opening, there was 82% satisfaction for the catheter of PVC, pre lubricated with glyserol (C2). Concerning sliding, there was 92% satisfaction, with median of 4,0 for hydrophilic polyuretane catheter, pre lubricated with PVP (C1). Concerning the catheter withdrawal, (C2) presented 86% satisfaction. Concerning sensibility, 40% participants presented discomfort with (C2) and 70% presented satisfaction with (C1). On the scoreboard , it was observed 90% satisfaction for (C2) and 86% for (C1) in the set for CIVC. Probably, opening, insertion, withdrawal, ease of transport, hygiene and the non-touch techinique were fundamental to the satisfaction with the set for CIVC. Data Analysis – Data were analysed through descriptive measures (median, percentile), as well as comparison tests for the evaluation of the kind of catheters used. Conclusion – The set presented a percentual of satisfaction on insertion, sliding and withdrawal. Opinion like ‘difficult ‘, was used referring to rigidity on insertion and withdrawl. This evaluation of teaching learning is individualised and considers the difficulties and preferences of paticipants. This information can be determining for your the adherence to CVlL